Implementation of Augmented Reality In Biology Learning: Its Effect on Learning Motivation and Retention - Tamam, Badrud; Qomaria, Nur (LPPM Undiksha, 2023)
One of the causes of low motivation and retention is the inaccuracy of the learning strategies applied. Therefore, it is necessary to update learning in order to be able to provide digital skills to students through the implementation of technology. This study aims to analyze the effect of implementing augmented reality on learning motivation and student retention in biology learning. This research is a quasi-experimental study with a Non-equivalent Pretest-Posttest Control Group Design. The research was conducted in class X SMA with a total sample of 65 students. The selection of samples was done randomly. Learning motivation was measured using a questionnaire of 36 question items and a Likert scale of 5 points. Retention was measured using an essay test. The test results were then measured using rubric with a scale of 0-4. Data were analyzed using a single ANCOVA with a pretest as the covariate. The results showed a significant effect of AR implementation on students' motivation and retention in biology learning. These results indicate that AR can be a solution as a pedagogical resource to increase motivation and empower retention.